Cytotoxicity of dimethyl sulfoxide (DMSO) in direct contact with odontoblast-like cells. Issue 4 (April 2015) - Hebling, J.; Bianchi, L.; Basso, F.G.; Scheffel, D.L.; Soares, D.G.; Carrilho, M.R.O.; Pashley, D.H.; Tjäderhane, L.; de Souza Costa, C.A.
Highlights: Approaches to improve the hybrid layer and bond strength have been developed. 5% DMSO is able to inactivate human gelatinases MMP-2 and MMP-9. Evaluation the possible toxic effect of DMSO against the pulp tissue. Low concentrations of DMSO did not evoke any substantial cytopathic effect. Abstract: Objectives: To evaluate the cytotoxicity of dimethyl sulfoxide (DMSO) on the repair-related activity of cultured odontoblast-like MDPC-23 cells. Methods: Solutions with different concentrations of DMSO (0.05, 0.1, 0.3, 0.5 and 1.0 mM), diluted in culture medium (DMEM), were placed in contact with MDPC-23 cells (5 × 104 cells/cm 2 ) for 24 h. Eight replicates ( n  = 8) were prepared for each solutions for the following methods of analysis: violet crystal dye for cell adhesion (CA), quantification of total protein (TP), alizarin red for mineralization nodules formation (MN) and cell death by necrosis (flow cytometry); while twelve replicates ( n  = 12) were prepared for viable cell number (Trypan Blue) and cell viability (MTT assay). Data were analyzed by ANOVA and Tukey or Kruskal–Wallis and Mann–Whitney's tests ( p  < 0.05). Results: Cell viability, adhesion and percentage of cell death by necrosis were not affected by DMSO at any concentration, with no statistical significant difference among the groups. A significant reduction in total protein production was observed for 0.5 and 1.0 mM of DMSO compared to the control while increased mineralized nodules formation was seen only for 1.0 mM DMSO. Significance: DMSO caused no or minor cytotoxic effects on the pulp tissue repair-related activity of odontoblast-like cells.